Private and civil law in the Russian Federation : essays in honor of F.J.M. Feldbrugge - Simons, William B.; Feldbrugge, F. J. M. (Ferdinand Joseph Maria), 1933- (Law in Eastern Europe, 2009)
Contains proceedings of the second and third Institute of East European Law anniversary conferences. This guide is suitable for those interested in law in Eastern Europe in particular and in society, both in Russia as well as in the region, in general.